A construção do conhecimento organizacional segundo a abordagem da semiótica peirceana - Coelho, Tatiene Martins [UNESP]; Valentim, Marta Lígia Pomim [UNESP]; De Almeida, Carlos Cândido [UNESP] (University Library System, University of Pittsburgh, 2017)
Objective. To present an initial contribution of the explanation of Peirceana Semiotics on the process of knowledge construction in organizations. Method. In the study we used the exploratory research with the support of a bibliographic review about the subject. Results. The applicability of Phenomenology and Semiotics in organizations, in which subjects relate through sign exchange sharing language. It can be said that the concepts proposed by Peirce remain useful to the theoretical analysis of knowledge. Conclusions. The present study made it possible to explain the creation of meaning in organizations, which happens to the detriment of the need to respond to changes in everyday situations and enables the transformation of tacit knowledge into explicit knowledge. However, for this process to be effective, it is necessary to recognize that the creation of knowledge must be guided by the pragmatic test of generated representations and the formation of new mental habits.
The construction of organizational knowledge according to Peircean's semiotic approach
Keywords: Knowledge construction; Knowledge management; Organizational environments; Peirce's semiotics